Influence of EWOM, Perceived Risk and Trust on Purchase Intention in M-Commerce (International Journal of Scientific Research and Management (IJSRM), 2025)
Using the Information Adoption Model (IAM) as the theoretical framework, the research examines how the quality, quantity, and credibility of online reviews influence perceived usefulness, which in turn affects trust, perceived risk, and the adoption of information that drives purchase intention in the context of local skincare products in Indonesia. Data were collected from 264 respondents who have seen online reviews of local skincare products marketed through m-commerce platforms, selected using a judgmental sampling technique. The data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both the quality and quantity of eWOM significantly influence perceived usefulness. In turn, perceived usefulness positively affects trust and helps reduce perceived risk. Trust is found to be a key factor in facilitating information adoption, which ultimately leads to stronger purchase intentions. This study offers practical insights for skincare brands and marketers by highlighting the importance of managing eWOM and building consumer trust to enhance online purchase decisions in the growing m-commerce environment.